Improving students’ ability to understand mathematical concepts through peer tutor type cooperative learning models in PP. Syariful Hidayah - Kartika Harahap; Nurlina Ariani Harahap (SAINTIS Publishing, 2022)
The purpose of this study was to determine the increase in mathematics learning outcomes through peer tutor type cooperative learning models in class IX.1 PP students. Shariful Hidayah. This study used three rounds of classroom action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is class IX.1 PP students. Shariful Hidayah. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that the learning outcomes of students experienced an increase from the pre-cycle, cycle I to cycle II, namely, pre-cycle (53.52%), cycle I (70.67%), and cycle II (79.74%). The conclusion of this study is that the peer-tutor-type cooperative learning model has a positive effect on the learning outcomes of PP students. Syariful Hidayah, as well as this learning method can be used as an alternative to learning mathematics.